Geochemical and Hf-Pb-Sr-Nd isotopic constraints on the origin of the Amsterdam-St. Paul (Indian Ocean) hotspot basalts - Doucet, Sonia; Weis, Dominique; Scoates, James; Debaille, Vinciane; Giret, André (2004)
The Amsterdam-St. Paul (ASP) Plateau is a recent (≤5 Ma) volcanic rise constructed along the Southeast Indian Ridge (SEIR) by the combined effects of a relatively small mantle plume and a mid-oceanic ridge. The Amsterdam and St. Paul islands are located 100 km away from each other and formed during the last 0.4 Myr; they are the only subaerial features of the ASP Plateau and the two islands are structurally separated by the presence of a SW-NE transform fault. New geochemical analyses and Hf-Pb-Sr-Nd isotopic compositions of 20 basaltic rocks from Amsterdam and St. Paul Islands constrain the nature and origin of the sources involved in the genesis of the ASP hotspot basalts. Aphyric basalts from St. Paul are mildly alkalic, incompatible element-enriched and highly fractionated; they are distinct from the tholeiitic basalts from Amsterdam, from the recently discovered Boomerang active seamount on the ASP Plateau, and from the Kerguelen Archipelago basalts on the Antarctic Plate. The St. Paul and Amsterdam basalts have very limited isotopic variations with distinct 206Pb/ 204Pb, 207Pb/204Pb, 208Pb/ 204Pb, and 176Hf/177Hf isotopic compositions (19.08±0.07, 15.61±0.02, 39.45±0.12, 0.28313±0.00003 for Amsterdam, and 18.70±0.08, 15.56±0.01, 38.87±0.05, 0.28306±0.00002 for St. Paul, respectively) that are not compatible with any direct contribution of the enriched Kerguelen plume end-member. Pb-Nd-Sr isotopic compositions of the St. Paul basalts appear consistent with simple binary mixtures between heterogeneous ambient upper mantle and a highly radiogenic Pb plume component (the ASP plume end-member), particularly expressed in the isotopic compositions of the Amsterdam basalts. However, the Amsterdam basalts have distinctly higher εHf than the St. Paul basalts (+13 and +10, respectively) for a given εNd (+4) and are inconsistent with such a simple binary mixing scenario. Isotopic systematics in the Amsterdam and St. Paul basalts indicate that the Amsterdam and St. Paul volcanoes were formed by sampling isotopically ...